Recent treatment technologies for Alzheimer disease: a review - Dhaidan, Asmaa S.; Al-Azzawi, Shafq (Pharmakeftiki, 2025)
Alzheimer disease (AD) is a progressive neurodegenerative disorder characterized by memory loss, confusion, and behavioural changes. It primarily impairs brain function, leading to a gradual decline in cognitive abilities such as thinking, reasoning, and problem-solving. As the most common cause of dementia, AD reflects a deterioration in mental faculties severe enough to disrupt daily activities. The disease advances slowly and typically worsens over time. Currently available pharmacological treatments address only the symptoms of AD, largely due to the restrictive nature of the blood-brain barrier (BBB), which impedes the entry of therapeutic agents into the central nervous system. This review summarizes recent technological advances in AD treatment, focusing on monoclonal antibody (mAb) therapies, nanotechnology-based delivery systems, and gene-editing approaches. mAb therapies encompass passive immunotherapy and tau-targeting interventions aimed at mitigating pathological protein accumulation. Nanotechnology-based strategies for AD include the use of nano-carriers, nano-polymers, dendritic nanoparticles, liposomes, and exosomes. These platforms have demonstrated enhanced drug delivery across the BBB with minimal adverse effects. Furthermore, gene-editing techniques target specific genetic variants, such as apolipoprotein E4 (ApoE4), which are implicated in both early- and late-onset forms of AD. Gene-editing is emerging as a promising therapeutic modality for correcting dominant mutations associated with AD pathogenesis. Despite these advances, further research and clinical trials are essential in order to develop and validate novel treatment strategies for AD.